Five questions about the digital services tax to Pierre Moscovici - Matthias Bauer (European Centre for International Political Economy (ECIPE), 2018)
The European Commission has recently proposed to upend decades of international tax cooperation and introduce a new three percent tax on corporate turnover from digital advertising and online intermediation services. The proposal is not just remarkable for the actual design of the tax; it is equally notable that the digital services tax is proposed without any supporting evidence that it is in EU Member States' economic and fiscal interest to tax digital business models differently. The proposed tax on turnover would undoubtedly have direct and indirect consequences for many firms and for economic activity, and it is neither reasonable nor credible to assume that this tax would not have enough impact on EU economies to warrant a full tax-economic impact analysis. The Commission's own impact assessment was sharply criticised by the EU's Regulatory Scrutiny Board. Simplistic and narrow in scope, the Commission's assessment fails to take account of the most common consequences of business taxes and any policymaker who cares about the health of Europe's economy should send back these proposals to the Commission and ask for a response to the following five questions: first, what is the incidence of the proposed digital services tax - that is, who will actually carry the economic burden of the tax? Second, won't the digital services tax impact on downstream output and offline sales? Third, won't the digital services tax particularly hurt SMEs and micro businesses and change competition between large and small firms? Fourth, won't a digital services tax effectively become a tax on investment in the EU? And lastly, won't this tax become a levy on innovation, economic renewal and economic convergence in the EU?
Keywords: 330